Pengawasan dan Koordinasi Sertifikasi Halal - Harahap, Rabiah (Universitas Muhammadiyah Sumatera Utara, 2018)
The main factor which is the weakness of consumers is the level of consumer awareness of their rights is still low. This is mainly due to low consumer education. Therefore the consumer protection law is intended to be a strong legal foundation for government and non-governmental consumer protection institutions to make efforts to empower consumers through coaching and educating consumers. This writing uses normative juridical legal research methods (normative research) with descriptive analytical research specifications that use secondary data. The procedure of data collection is in the form of documentation of notes or quotations, search of legal literature, books and others related to the identification of problems both offline and online which are then analyzed through the content analysis method with a focus on the issue of how supervision and coordination of halal certification. The results of the study, it is known that the Consumer Protection Act states that businesses are prohibited from producing or trading goods or services that do not follow the provisions of halal production (Law No. 23 of 2014 concerning Guaranteed Halal Products).